2003
DOI: 10.1021/ja035030r
|View full text |Cite
|
Sign up to set email alerts
|

Radical Cage Effects in the Photochemical Degradation of Polymers:  Effect of Radical Size and Mass on the Cage Recombination Efficiency of Radical Cage Pairs Generated Photochemically from the (CpCH2CH2N(CH3)C(O)(CH2)nCH3)2Mo2(CO)6 (n = 3, 8, 18) Complexes

Abstract: This study explored the effect of radical size, chain length, and mass on the cage recombination efficiency of photochemically generated radical cage pairs. Radical cage pairs containing long-chain radicals of the type [(CpCH(2)CH(2)N(CH(3))C(O)(CH(2))(n)CH(3))(CO)(3)Mo*, *Mo(CO)(3)(CpCH(2)CH(2)(CH(3))NC(O)(CH(2))(n)CH(3))] were generated in hexanes/squalane solution by photolysis (lambda = 546 nm) of the Mo-Mo bonds in (CpCH(2)CH(2)N(CH(3))C(O)(CH(2))(n)CH(3))(2)Mo(2)(CO)(6) (n = 3, 8, 18). The cage recombina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
21
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 25 publications
2
21
0
Order By: Relevance
“…It was concluded that polymer free volume V f was the dominant factor controlling the diffusion of the benzyl and other radicals, and, therefore, the kinetics of cage recombination and cage escape [10]. An increase of size (mass) of many atoms radicals leads to a decrease of their cage escape and to an increase of the cage effect [18].…”
Section: Cage Effect Values By Product Analysismentioning
confidence: 99%
“…It was concluded that polymer free volume V f was the dominant factor controlling the diffusion of the benzyl and other radicals, and, therefore, the kinetics of cage recombination and cage escape [10]. An increase of size (mass) of many atoms radicals leads to a decrease of their cage escape and to an increase of the cage effect [18].…”
Section: Cage Effect Values By Product Analysismentioning
confidence: 99%
“…The detailed procedure for obtaining F cP by the steadystate method has been previously described [15]. In brief, values for F cP were extracted from quantum yield measurements of the reaction in Eq.…”
Section: The Effect Of Wavelength On F Cpmentioning
confidence: 99%
“…The intermediate, ethyl (4aS,3,4,4a,5,indole-2-carboxylate (12), is prepared on kilograms scale in 31% overall yield and >99% ee. (6bR,10aS)-3- 3,6b,7,8,9,10,4':4,5]pyrrolo[1,2,3-de]quinoxaline hydrochloride (16-HCl) is obtained through reductamination reaction, palladium catalyzed cyclization and ester hydrolysis in 60% yield over 3 steps and >98% purity. Lumateperone tosylate is produced on 20 g scale in 65% yield over 2 steps and >99% purity (HPLC).Purification methods of the intermediates and the final product involved in the route are developed.Lumateperone tosylate (1, Scheme 1, Caplyta TM ), developed by Intra-Cellular Therapies, Inc., was approved by the U.S. Food and Drug Administration (FDA) in Dec. 2019, for the treatment of schizophrenia in adults.…”
mentioning
confidence: 99%
“…The intermediate, ethyl (4aS,3,4,4a,5,indole-2-carboxylate (12), is prepared on kilograms scale in 31% overall yield and >99% ee. (6bR,10aS)-3- 3,6b,7,8,9,10,4':4,5]pyrrolo[1,2,3-de]quinoxaline hydrochloride (16-HCl) is obtained through reductamination reaction, palladium catalyzed cyclization and ester hydrolysis in 60% yield over 3 steps and >98% purity. Lumateperone tosylate is produced on 20 g scale in 65% yield over 2 steps and >99% purity (HPLC).…”
mentioning
confidence: 99%